Pembimbingan Pembuatan Pot Tumbuhan dari Daur Ulang Kain Bekas dan Semen - Mutia Lisya; Nuryasin Abdillah; Lis Hafrida; Oscar Theo Beldin S (Penerbit Goodwood, 2022)
Purpose: In particular, this activity aims to provide education to BKG 5 (Bundo Kanduang Gonjong 5) in the use of processed upcycled materials, with the aim of training creativity and skills in processing used materials around them to be converted into ready-to-use products so as to reduce waste by providing guidance on processing waste clothing or used towels into ornamental plant pots. This training is also expected to be a savings in the purchase of ornamental plant pots which are currently rife among people. Method: The methods used are lecture and question and answer methods, demonstration methods, and non-formal discussion methods. Result: As a result, during the training activities, the participants participated with great enthusiasm for all the material that had been given by the presenters which was then followed by a question section. In addition, the participants had new knowledge about the utilization of unused used goods in the surrounding environment to be reprocessed into useful products. Conclusion: The implementation of community service activity programs through ornamental plant pot training can be carried out properly according to the plan. It is proven by the enthusiasm shown by the participants with the attendance indicators exceeding the target where many people took part in this activity.